We the people : - Patterson, Thomas E. (McGraw-Hill, 2004)
This concise yet comprehensive book provides a positive, lively, future-oriented narrative introduction to American government and politics. We the People presents material with a currency and relevancy that captures the vivid world of real-life politics. In addition, the text challenges readers to think critically; by giving contextual understanding of major concepts and issues, it encourages them to think about the implications for society and themselves. We the People delves deeper into the basics than most brief books, and each of the 17 chapters (including 3 policy chapters) concludes with a reading selection (each from a different paper around the country) and an extensive bibliography. The seventh edition has been thoroughly updated to capture recent developments, including the 2006 elections.